2019
DOI: 10.1097/md.0000000000014937
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for acquisition and mortality of multidrug-resistant Acinetobacter baumannii bacteremia

Abstract: Bloodstream infection caused by Acinetobacter baumannii has become a major clinical concern, especially multidrug-resistant A baumannii (MDRAB). The aim of this study was to identify the risk factors of nosocomial acquired MDRAB bacteremia and to determine the risk factors related to the mortality of patients with MDRAB bacteremia. Patients with nosocomial acquired A baumannii bacteremia were enrolled between January, 2013 and December, 2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 43 publications
4
49
0
2
Order By: Relevance
“…The use of mechanical ventilation, ICU stay and thrombocytopenia may cause higher mortality. Previous studies demonstrated that the mortality risk factors associated with poor prognosis include older age, severity of the underlying disease, septic shock, a high Pitt bacteremia score, previous surgery, mechanical ventilation, and inappropriate antimicrobial treatment [12,[22][23]. The ICU was the highest risk unit of this nosocomial outbreak of MDR-AB, which could subsequently disseminate within the hospital [24].…”
Section: Discussionmentioning
confidence: 99%
“…The use of mechanical ventilation, ICU stay and thrombocytopenia may cause higher mortality. Previous studies demonstrated that the mortality risk factors associated with poor prognosis include older age, severity of the underlying disease, septic shock, a high Pitt bacteremia score, previous surgery, mechanical ventilation, and inappropriate antimicrobial treatment [12,[22][23]. The ICU was the highest risk unit of this nosocomial outbreak of MDR-AB, which could subsequently disseminate within the hospital [24].…”
Section: Discussionmentioning
confidence: 99%
“…The use of mechanical ventilation, ICU stay, and thrombocytopenia have all been associated with higher mortality. Previous studies demonstrated that the mortality risk factors associated with poor prognosis include older age, the severity of the underlying disease, septic shock, a high Pitt bacteremia score, previous surgery, mechanical ventilation, and inappropriate antimicrobial treatment [21,42,43]. The ICU has been identi ed as the unit at the highest risk of the nosocomial outbreak of MDR-AB [44].…”
Section: Discussionmentioning
confidence: 99%
“…High resistance and virulence of bacteria are the main factors associated with high mortality in patients with bloodstream infections [10,21]. Some studies reported that the patient's condition, previous exposure to antimicrobial (especially broad-spectrum antibiotics), previous colonization with A. baumannii, increased Pitt bacteremia score, being in the intensive care unit (ICU), and recent invasive procedures are risk factors associated with MDR acquisition in A. baumannii bloodstream infection [22][23][24].…”
mentioning
confidence: 99%
“…The potency of A. baumannii as a successful pathogen can be elaborated by the high number of deaths associated with its infection. A recent finding showed that bacteremia caused by multidrug-resistant (MDR) A. baumannii exhibited 56.2% mortality rate among infected patients ( Zhou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%